Analysis of the Relationship Between Economic Policy Package Volume XV To Service Quality and Custom Clearance in the Furniture Industry in Indonesia - Johanes Ronaldy Polla; Tommy Julius; Tan Agus Setiawan; Abdul Qadir A Syakur (Journal of Business, Management, & Accounting, 2022)
The economic policy package volumes XV set out coupled with export and import activities in Indonesia. This research aims to analyze the effect of the economic policy package volumes XV committed by the Government against the Service Quality and Custom Clearance on the furniture industry companies in Indonesia. The data collected through interviews. Analysis of the method used is descriptive analysis method. The respondents in this study are the manager of forwarding company in Indonesia, owner of furniture company, and operational staff from customs. The result of the research shows that the economic policy package volumes XV undertaken by the Government have an impact on the Service Quality provided as well as Custom Clearance process within the scope of the furniture industry in Indonesia.